Disruption of cancer cell functions by task-specific drug perturbations - Ahmed, Mahmoud; Kim, Deok Ryong (Frontiers in Pharmacology, 2022)
Cancer expands clonally, capitalizing on the variations between growing cells. Cancer cells specialize in one or more functions to gain an advantage. This study examined the prediction that cells would be vulnerable to drugs that perturb their specific tasks. We analyzed the correlation between gene expression and the response to drug perturbations in different cancer cells. Next, we assigned every cancer cell to an archetype based on gene expression. Finally, we calculated the enrichment of the cancer hallmarks gene sets in each cell, archetype, and in response to drug treatment. We found that the extremes of gene expression were susceptible to change in response to perturbations. This correlation predicted the growth rate inhibition of breast cancer cells. Cancer hallmarks were enriched differently in the archetypes, and this enrichment predicted the cell's response to perturbations. We present evidence that specialized cancer cells are sensitive to compounds that perturb their tasks.